Development of shape memory alloy hybrid yarns for adaptive fiber-reinforced plastics. Issue 8 (April 2019) - Ashir, Moniruddoza; Nocke, Andreas; Cherif, Chokri
The application of shape memory alloys (SMAs) for the development of adaptive fiber-reinforced plastics has been expanding steadily in recent years. In order to prevent matrix damage and optimize the actuating potential of SMAs during the process of thermally induced activation, a barrier layer between SMAs and the matrix of fiber-reinforced plastics is required. This article approaches the textile technological development of SMA hybrid yarns as a core–sheath structure using friction spinning technology, whereby the SMA serves as the core. Four types of hybrid yarns are produced by varying the number of process stages from one to three, as well as the core and sheath materials. The decoupling of the SMA from fiber-reinforced plastics is crucial for optimizing the actuating potential of SMA, thus it is tested by means of the pull-out test. Although the material loss coefficient increases by raising the number of process stages, the three-stage processing of SMA hybrid yarn with an additional glass roving is found to be the most suitable variation for decoupling SMA from the matrix of fiber-reinforced plastics.